Nanocomposites of CsPbBr3 perovskite nanocrystals in an ammonium bromide framework with enhanced stability. Issue 30 (20th July 2017) - Lou, Sunqi; Xuan, Tongtong; Yu, Caiyan; Cao, Mengmeng; Xia, Chao; Wang, Jing; Li, Huili
Abstract : The CsPbBr3 @NH4 Br nanocomposites were successfully synthesized through ion exchange. The nanocomposites possessed a special core@shell structure and exhibited a high absolute PLQY, long lifetime, good water resistance and excellent thermal stability. Abstract : Herein, we report a new highly luminescent material, a CsPbBr3 @NH4 Br (CPBr–NB) nanocomposite, formed via an ion-exchange reaction, which can reach up to a few micrometers in size. The CPBr–NB solid-state luminophores with a unique core@shell structure effectively avoid photoluminescence quenching and maintain excellent optical properties of the perovskite nanocrystals. Most importantly, the nanocomposite exhibits excellent water resistance and thermal stability. Such superior optical merits endow them with promising potential in lighting and displays.